Biocompatible long-circulating star carboxybetaine polymers. Issue 3 (18th November 2014) - Lin, Weifeng; Ma, Guanglong; Ji, Fangqin; Zhang, Juan; Wang, Longgang; Sun, Haotian; Chen, Shengfu
Abstract : Polyethylene glycol (PEG) is considered to be the most effective material to prolong the circulation time of nanoparticles by reducing non-specific protein adsorption in blood. Abstract : Polyethylene glycol (PEG) is considered to be the most effective material to prolong the circulation time of nanoparticles by reducing non-specific protein adsorption in blood. However, it is recognized that PEG decomposes in most physiological solutions, and an anti-PEG antibody has been detected in some normal blood donors as a response to injection with PEGylated polymer particles. Zwitterionic polymers are potential alternatives to PEG for biomedical applications because of their super resistance to non-specific protein adsorption. Thus, finding one polymer with a long circulation time and resistance to the immune response is of significant importance. Here, we prepared four star carboxybetaine polymers of different molecular weights via atom transfer radical polymerization (ATRP) from a β-cyclodextrin (β-CD) initiator for investigating the biocompatibility of carboxybetaine polymer, a typical zwitterionic polymer. The circulation half-life of the largest star polymer (123 kDa) in mice was prolonged to 40 h in vivo, with no appreciable damage or inflammation observed in the major organ tissues. Furthermore, the circulation time of repeat injections showed similar results to the first injection, with no obvious increase in the amount of antibody in blood. The internalization of the star carboxybetaine polymers by macrophage cells was a relatively slow process. The high cell viability in the presence of star carboxybetaine polymers up to 2 mg mL −1 was maintained. The hemolytic activity of the star carboxybetaine polymers at 5 mg mL −1 was almost undetectable. In vitro results prove a key prediction of excellent biocompatibility in vivo . All the results suggest that the carboxybetaine polymer, perhaps even most of the zwitterionic ones, might be a good alternative to PEG in the development of a drug delivery system.